Measuring restrictions on FDI in services in developing countries and transition economies (UN New YorkUS, 2006)
Quantifies and analyzes restrictions on inward foreign direct investment (FDI) in the services sector of developing countries and economies in transition, using a methodology developed in a recent study of OECD countries. Suggests that Latin America and economies in transition generally have relatively low levels of restrictions, whereas higher levels of restrictions are found in developing Asia.
Keywords: FOREIGN INVESTMENT